1986
DOI: 10.1111/j.1469-8137.1986.tb00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rates of Photosynthesis in Localized Regions of a Barley Leaf Infected With Brown Rust

Abstract: SUMMARYThe rate of photosynthesis was examined in whole leaves of barley infected with brown rust {Puccinia hordei Otth.) and within localized regions of the infected leaf, within brown rust pustules and in regions between them, from flecking to green island formation. In addition, oxygen evolution was measured from localized regions of a rusted leaf after feeding with inorganic phosphate (Pi) to investigate the hypothesis that fungal sequestration of Pi from the host cytoplasm may, totally or partially, be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
2
8

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 24 publications
4
48
2
8
Order By: Relevance
“…Although a reduced concentration of Pi in the cytosol may be a characteristic of leaves infected with biotrophic fungi (Whipps & Lewis, 1981), phosphate does not aflFect photosynthesis in barley infected with brown rust (Scholes & Farrar, 1986) or with powdery mildew (J. F. Farrar & J. Carroll, unpublished data). Respiration in mildewed barley is not restricted by inadequate substrate supply: sugars do not increase it unless plants have been darkened for 48 h and the respiration of diseased leaves reduced by 30 % in consequencethen sugars only restore control respiration rates.…”
Section: Resultsmentioning
confidence: 99%
“…Although a reduced concentration of Pi in the cytosol may be a characteristic of leaves infected with biotrophic fungi (Whipps & Lewis, 1981), phosphate does not aflFect photosynthesis in barley infected with brown rust (Scholes & Farrar, 1986) or with powdery mildew (J. F. Farrar & J. Carroll, unpublished data). Respiration in mildewed barley is not restricted by inadequate substrate supply: sugars do not increase it unless plants have been darkened for 48 h and the respiration of diseased leaves reduced by 30 % in consequencethen sugars only restore control respiration rates.…”
Section: Resultsmentioning
confidence: 99%
“…Rubisco, an increase in host and/or fungal resin many host/pathogen interactions, photosynthesis piration, or fungal sequestration of Pi from the host may be enhanced initially but, in most systems, the cytoplasm leading to a reduction in the recycling of rate declines and chlorophyllis lost from the tissue as Pi in the chloroplast (see Ayres, 1981; the disease develops (Ahmad, Farrar & Whitbread, Lewis, 1987). In addition, biotrophs alter trans-1983; Scholes & Farrar, 1986). A number of location patterns of carbohydrates in infected tissue by decreasing export from, and in many cases, increasing import of sucrose into infected leaves (Whipps & Lewis, 1981;Farrar & Lewis, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in Chl a: Chl b ratio was due to an increase in Chl b which represented an increase in lightharvesting chlorophyll (Scholes and Farrar, 1985). It is reported that the decrease in photosynthetic activity is due to fluctuations in the concentrations of total chlorophyll and Chl a: Chl b ratio (Sharkey, 1985;Scholes and Farrar, 1986). The damage to the electron transport chain and an inhibition of non-cyclic photophosphorylation are also the major cause of reduction in chlorophyll concentration and in turn the photosynthetic activity after powdery mildew infestation (Magyarosy et al, 1976;Sharkey, 1985;Scholes and Farrar, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that the decrease in photosynthetic activity is due to fluctuations in the concentrations of total chlorophyll and Chl a: Chl b ratio (Sharkey, 1985;Scholes and Farrar, 1986). The damage to the electron transport chain and an inhibition of non-cyclic photophosphorylation are also the major cause of reduction in chlorophyll concentration and in turn the photosynthetic activity after powdery mildew infestation (Magyarosy et al, 1976;Sharkey, 1985;Scholes and Farrar, 1986). It has been suggested that an increase in host and/or fungal respiration is partially responsible for the reductions in chlorophyll concentrations and photosynthesis in powdery mildew infected tissue (Farrar and Rayns, 1987).…”
Section: Resultsmentioning
confidence: 99%